The effectiveness of self-hypnosis to reduce the intensity of nausea vomiting in emesis patients - Kusuma, Wijaya; Sari, Yeni M.; Hami Seno, Budhi (International Journal of Research in Medical Sciences, 2024)
Background: Pregnancy triggers various physical and psychological changes, including common first-trimester symptoms like nausea and vomiting. Self-hypnosis can help alleviate these symptoms, offering an alternative treatment for pregnant women. Methods: This double-blind randomized controlled trial (RCT) included 44 pregnant women with gestational ages less than 20 weeks, selected through purposive and total sampling. Participants were divided into two groups: the treatment group (n=22) received self-hypnosis recordings with water sounds, while the control group (n=22) received recordings of water sounds only. Both groups listened to the recordings for 15 minutes each morning and night over a period of 4 weeks. The study took place in the Kedunggalar Health Center area from June to July 2023. The PUQE-24 instrument measured nausea and vomiting severity before the intervention and weekly for four weeks thereafter. Data were analyzed using independent sample t-test and repeated measures analysis of variance (ANOVA). Results: The treatment group experienced a statistically significant reduction in nausea and vomiting intensity, as indicated by PUQE-24 scores, at week I (p=0.013), week II (p=0.000), week III (p=0.000), and week IV (p=0.000). The treatment group showed a greater reduction in mean PUQE-24 scores compared to the control group (p<0.05). Clinically, nausea and vomiting intensity decreased from moderate to mild or none in the treatment group, while the control group showed no significant changes. Conclusions: Self-hypnosis is effective in reducing the intensity of nausea and vomiting in patients with emesis gravidarum.